Karakteristik Kuantitatif Kerbau (Bubalus bubalis) dalam Sistem Pemeliharaan Ekstensif di Gunung Sangiang Nusa Tenggara Barat - wandira, ica ayu; dohi, muhammad; sadia, I nyoman; yanuarianto, oscar; firhamsah, ikhwan (Jurnal Sains Riset, 2025)
Buffalo farming in remote areas such as Mount Sangiang, Bima Regency, West Nusa Tenggara, is still managed traditionally, with limited access to scientific information. This study aimed to analyze the quantitative traits of buffaloes raised in this volcanic environment, including body weight, body dimensions, and leg length. A descriptive observational study was conducted on 30 male and female buffaloes of various age groups. The results show morphometric differences influenced by genetic, hormonal, environmental, physical activity, and reproductive factors. Males exhibit faster skeletal growth, while adult females have greater body weight and chest girth. These findings support morphometric analysis for selection and conservation.